Iowa Birdline update, November 26, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for November 26, 1990. Highlights of the update include sightings of a Prairie Falcon, a Snowy Owl, a Eurasian Tree Sparrow, two Scoter species, and three Gull species. Also included are handwritten notes with sightings of Snowy Owls, a female Pine Siskin, and a female Merlin. Epson - sheet feed/flatbed